Nevus of Ota Involving Palate: Case Reports and Review - Ajay Pratap Singh Parihar; Anjana Bagewadi; Vaishali Keluskar; Arvind Shetti (Wolters Kluwer Medknow Publications, 2007)
Nevus of Ota is a rare dermal melanocytosis. 2 case reports of this rare leson is reported in Indian patients.